Meningkatkan Kompetensi Pengetahuan IPS Menggunakan Model Problem Based Learning Berbantuan Media yang Diproyeksikan pada Siswa - Widurata, I Kadek Prabu; Ni Wayan Sunasih; I Wayan Sujana (Universitas Pendidikan Ganesha, 2023)
The condition of a pluralistic society will potentially be prone to social conflict, thus disrupting the integrity of harmonious social relations in society. The research aims to develop English language teaching materials based on multicultural values in higher education. This research uses research and development involving Analysis, Design, Development, and implementation (ADDIE) models and mixed methodology. In collecting data, several instruments were used: observation, in-depth interviews, Focus Group Discussions (FGD), document analysis, and questionnaires. This research involved student participants and lecturers. The data analysis technique used is qualitative and quantitative descriptive analysis. The findings of this research show that in English textbooks, readings and twenty exercises that contain multicultural values are expected to be found. In the English for Agribusiness textbook, researchers did not find multicultural values. In addition, the results of the needs analysis show that teachers and students need to provide appropriate techniques and strategies for teaching English through multicultural values. The validity results show that multicultural education can be taught using English material. Based on the effectiveness results, it shows that multicultural education is effective. Multicultural education needs to be involved by including multicultural values in English teaching materials, especially in universities. For future research, it is necessary to find English language teaching materials with other methodologies and specific fields at the higher education level.